2011
DOI: 10.1186/1471-244x-11-96
|View full text |Cite
|
Sign up to set email alerts
|

Major depressive disorder following terrorist attacks: A systematic review of prevalence, course and correlates

Abstract: BackgroundTerrorist attacks are traumatic events that may result in a wide range of psychological disorders for people exposed. This review aimed to systematically assess the current evidence on major depressive disorder (MDD) after terrorist attacks.MethodsA systematic review was performed. Studies included assessed the impact of human-made, intentional, terrorist attacks in direct victims and/or persons in general population and evaluated MDD based on diagnostic criteria.ResultsA total of 567 reports were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 54 publications
(132 reference statements)
0
56
2
1
Order By: Relevance
“…Thus, our findings identify increased depression as one mechanism to greater alcohol use in these demographic groups. Similarly, Salguero, Fernandez-Berrocal, Iruarrizaga, Cano-Vindel, and Galea (2011) in a review of U.S. and international studies found women more likely to develop a major depressive disorder following terrorist attacks.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, our findings identify increased depression as one mechanism to greater alcohol use in these demographic groups. Similarly, Salguero, Fernandez-Berrocal, Iruarrizaga, Cano-Vindel, and Galea (2011) in a review of U.S. and international studies found women more likely to develop a major depressive disorder following terrorist attacks.…”
Section: Discussionmentioning
confidence: 90%
“…Para a confirmação do diagnóstico, indaga-se ainda sobre alterações psicomotoras, cognitivas e somáticas 2 . Investigações sobre as causas da depressão sugerem uma etiologia complexa, pois vulnerabilidades individuais (biológicas e psicológicas) são influenciadas pelo macroambiente 3,4 .…”
Section: Introductionunclassified
“…We found no significant differences in contrast to previous studies, which showed that residents living in areas affected by terrorism suffered from depression. 33,34 There were many factors associated with the depressive symptoms of residents within these terrorism areas such as; financial hardship, material deprivation and lower social support. 35 Due to the diversity of these factors, the prevalence of depression between this study and previous studies was different.…”
Section: Discussionmentioning
confidence: 99%